Migrasi dalam perspektif semiotika etnodemografi dan gender: Kasus masyarakat di hulu Sembakung, Kalimantan Utara - Puji Hastuti (Jurnal Kependudukan Indonesia, 2022)
State border areas are often considered rigid and isolated spaces, and this assumption is usually not in accordance with reality on the ground. Communities in border regions of Indonesia have kinship ties across countries, such as life across borders that occur in the upper Sembakung River. The river flows in the border area of North Kalimantan and upstream in Sabah, Malaysia. The problem occurs when to conduct social interaction, the population in the border area must conduct various negotiations on the rules of the spatial state. The natural morphology of the Sembakung River crossing connects the ethnic interactions of the population at the country's borderline, which is often assumed to threaten sovereignty. The concentration of state territory space, a legacy of colonial cartography, is not in line with the social boundaries of the population formed by the natural morphology of the Sembakung River channel, which provides space for residents to penetrate state boundaries. This paper explores cross-border interactions through the flow of the Sembakung River, which is strengthened by life cycle rites through the Mauss gift scheme, which is prone to creating marginalization of women. Cross-border social ties have penetrated rigid territorial boundaries. This situation resulted in the infiltration of economic commodities mobility intertwined with people's cultural activities in hulu Sembakung, a group of population with dual citizenship, and the practice of rites of exchange that are vulnerable to women's marginalization.